The Effect of Price, Land Area, and Education on Salak Farmers' Income in Pangu Village, North Sulawesi - Muhtadi, Muhamad Ammar; Safruddin, Safruddin (West Science Agro, 2024)
This research investigates the effect of market price, land area, and education on the income of salak farmers in Pangu Village, North Sulawesi, utilizing a quantitative research approach. Through a survey of 150 salak farmers and regression analysis using SPSS version 26, the study examines the relationships between these variables and farmers' income levels. The findings reveal that market price, land area, and education significantly influence farmers' income, with higher prices, larger landholdings, and higher education levels associated with increased income. These results underscore the importance of market conditions, land resources, and human capital in shaping the economic well-being of agricultural communities. The insights provided by this study can inform policy interventions and agricultural development initiatives aimed at promoting sustainable livelihoods and enhancing the prosperity of salak farmers in Pangu Village and similar rural areas.